ANALISIS PERENCANAAN SDM DALAM MEMPERKUAT KULTUR ORGANISASI PADA KANTOR BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KOTA GUNUNGSITOLI - Zalukhu, Noferlina; Hidayat Waruwu, Meiman; Lase, Delipiter; Mendrofa, Yupiter (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Balikpapan, 2024)
The purpose of this research is to determine the human resource (HR) planning implemented at the Gunungsitoli City Personnel and Human Resources Development Agency (BKPSDM) Office to strengthen organizational culture and the extent to which this implementation influences employee performance and creates a work environment that supports employee growth and development. . This research uses qualitative research with observation and interview data collection methods. Data analysis techniques use data processing, data presentation, data reduction and drawing conclusions. The results of research on HR planning at the Gunungsitoli City BKPSDM Office do not only focus on aspects of performance evaluation and compensation, but also emphasize efforts to create a work environment that supports employee growth and development. This approach is in line with concepts in modern human resource management theory.